Covid-19 as a Social Crisis and Justice Challenge for Cities - Haase, Annegret (Frontiers in Sociology, 2020)
The article deals with Covid-19 as a social crisis and justice challenge for cities. It describes how Covid-19 shines a spotlight on the uneven distribution of goods and burdens, opportunities and resources that we find in most of the world's cities today; inequality and justice challenges arise from both the crisis itself and some of the policy reactions to it, such as the stay-at-home orders and economic lockdowns. It shows how exposure and vulnerability to Covid-19 emerges mainly at the intersection between different dimensions of disadvantage and marginalization. The example of housing and green space provision is used to discuss this general argument in more detail. The article concludes that to overcome the social crisis and justice challenge posed by Covid-19, we have to tackle the underlying structures/mechanisms leading to inequitable outcomes in today's cities, and to re-think the social and justice yardsticks of current urban sustainability and resilience debates and strategies.